PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR GURU SD SARASWATI 4 DENPASAR - Diputra, Alvan Anggara; Rahyuda, Agoes Ganesha Rahyuda (E-Jurnal Manajemen; Vol 5 No 1 (2016), 2016)
This study aimed to examine the effect of transformational leadership and job satisfaction on organizational commitment and organizational citizenship behavior. Research was conducted on elementary school teachers Saraswati 4 denpasar. The sampling method used in this study sample is saturated. Data were collected using the method of observation, interviews and questionnaires. Respondents of the study a total of 35 primary school teachers Saraswati 4 Denpasar. Data analysis techniques used in this research is the analysis of pathways. These results indicate that (1) transformational leadership has a direct influence on organizational commitment, (2) job satisfaction has a direct influence on organizational commitment, (3) the commitment the organization has a direct influence on OCB, (4) transformational leadership has a direct influence on OCB. (5) job satisfaction has a direct influence on OCB, (6) transformational leadership influence on OCB through organizational commitment of elementary school teachers Saraswati 4 Denpasar, and (7) job satisfaction influence on OCB through organizational commitment of elementary school teachers Saraswati 4 Denpasar.
Keywords: kepemimpinan transformasional, kepuasan kerja, komitmen organisasi, organizational citizenship behavior